Prevalensi Wuchereria bancrofti Paska Pemberian Obat Pencegahan Massal Filariasis Limfatik di Wilayah Endemis Rendah Kota Pekalongan - Mara Ipa; Eksi Wijayanti; Hipokrates Hipokrates; Endang Puji Astuti; Yuneu Yuliasih (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2021)
Pekalongan district has completed mass drug administration (MDA) of lymphatic filariasis (LF) for two rounds but still remains positive for microfilariae (Mf rate) > 1%. This study aimed was to assess the prevalence of Wuchereria bancrofti and its association with sociodemographic among the adult community to the incidence of lymphatic filariasis. This study is an analytic study with a cross-sectional design. The prevalence of W. bancrofti was detected by the presence of circulating filarial antigen (CFA) using a filarial test strip (FTS). The study population consisted of an adult group living in ten villages in the Pekalongan district's low-endemic region, with 1804 samples collected from 72 clusters. Statistical analysis was performed to test the difference between variables. There were 13 (0.72%) positive W. bancrofti antigen samples out of 1804 total samples. Males were found to be infected at a higher rate than females (61.5%). The age of subjects infected with W. bancrofti was dominated in the range of 13-50 years as many as 9 people (69.2%). The proportion of positive CFA in Medono village with the highest proportion was 6 people (2.7%). There was no statistically significant difference between gender and age with LF cases, but it is significantly different by sub-district (p-value = 0.041). LF transmission occurred in border areas between high and low endemic LF areas. MDA implementation must be constantly supervised in required to address the elimination target.